Can propylthiouracil induce autoimmune-related immunotoxicity? - Bajkin, Ivana; Golubović, Sonja; Ičin, Tijana; Stepanović, Kristina; Ilić, Tatjana (Vojnosanitetski pregled, 2022)
Introduction. The use of propylthiouracil can be associated with mild adverse reactions, but severe complications such as agranulocytosis and vasculitis can also be seen. Direct toxicity and immune-mediated induction of anti-neutrophile cytoplasmic antibodies have been described as possible mechanisms responsible for agranulocytosis. The majority of vasculitis is antimyeloperoxidase antibodies associated, but the exact mechanism for anti-neutrophile cytoplasmic antibodies-associated vasculitis as an adverse effect of propylthiouracil treatment is still unclear. Case report. We presented a 61-year-old female patient with Graves’ disease who experienced a fever and throat pain two weeks after propylthiouracil therapy was initiated. Agranulocytosis alongside basal left-sided pneumonia was noted. Propylthiouracil was discontinued, and the treatment with broad-spectrum antibiotics was started, as well as Lugol’s solution, methylprednisolone, and granulocyte-colony stimulating factor. Further course of treatment was complicated by the occurrence of a generalized erythematous-papillomatous rash. The patient was diagnosed with agranulocytosis and antimyeloperoxidase, anti-neutrophile cytoplasmic antibodies positive vasculitis as an adverse effect of propylthiouracil. Conclusion. Patients presenting with concomitant agranulocytosis and anti-neutrophile cytoplasmic antibodies-associated vasculitis as a complication of propylthiouracil therapy for Graves’ disease are rare in clinical practice. Prompt discontinuation of the antithyroid drug is of great importance to reduce damage to target organs. Similarities in the pathogenesis of both conditions could be the potential explanation for these two adverse events occurring at the same time, which points out the need for a deeper understanding of this topic.